Quantification of topological concepts using ideals - Robert Lowen; Bart Windels (International Journal of Mathematics and Mathematical Sciences)
We introduce certain ideals of real-valued functions as a natural generalization of filters. We show that these ideals establish a canonical framework for the quantification of topological concepts, such as closedness, adherence, and compactness, in the setting of approach spaces.